1999
DOI: 10.1046/j.1365-2362.1999.00532.x
|View full text |Cite
|
Sign up to set email alerts
|

Angiogenesis extent and expression of matrix metalloproteinase‐2 and ‐9 correlate with upgrading and myometrial invasion in endometrial carcinoma

Abstract: These in situ data suggest that angiogenesis and degradation of extracellular matrix occur simultaneously with EC upgrading and advancing depth of invasion, and that EC cells and some host stromal cell populations cooperate in tumour progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
45
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(55 citation statements)
references
References 35 publications
7
45
2
Order By: Relevance
“…MMPs are an important group of zinc enzymes that are responsible for degradation of extracellular matrix components, such as collagen and proteoglycans, in normal embryogenesis and in many disease processes, such as arthritis and invasion by carcinoma (8,9). In our study, we showed that MMP-2 and MMP-9 mRNA and protein expressions were significantly down-regulated in LKB1-transfected MDA-MB-435 cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…MMPs are an important group of zinc enzymes that are responsible for degradation of extracellular matrix components, such as collagen and proteoglycans, in normal embryogenesis and in many disease processes, such as arthritis and invasion by carcinoma (8,9). In our study, we showed that MMP-2 and MMP-9 mRNA and protein expressions were significantly down-regulated in LKB1-transfected MDA-MB-435 cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…All these were related to upregulation of MMP-9 and Ets-1 levels. MMPs are important group of zinc enzymes that are responsible for degradation of extracellular matrix components such as collagen and proteoglycans in normal embryogenesis and in many disease processes such as arthritis and invasion by carcinoma (Iurlaro et al, 1999;Sillem et al, 1999). In the endometrium, it has been reported that some MMPs play important roles in endometrial physiologic characteristics and these roles are regulated by ovarian steroid hormones (Irwin et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Pro-MMP9 (7.5 ng) was incubated at 37°C with MMP3 (7.5 ng) in the absence or presence of TSP1 (0, 10, 30, 90, or 270 ng) in a total volume of 15 l for 2 h. The enzyme activity of the preincubated samples (10-l aliquots diluted to 50 l in gelatinase assay buffer) was determined by incubating at 37°C for 1 h and using [ ber of studies have documented that activation of MMP2 is associated with robust new vessel growth, while inhibition of its activity leads to depressed angiogenesis (46,47). Given the high degree of sequence homology between the TSR of TSP1 and TSP2, we have investigated whether TSP1 TSR also interacts with MMP2.…”
Section: Figmentioning
confidence: 99%